Factors Affecting Company's Capability in Performing Integrated Reporting: an Empirical Evidence from Indonesia - Putu Sukma Kurniawan; Made Arie Wahyuni (Assets: Jurnal Akuntansi dan Pendidikan, 2018)
This study examines the factors that affect the company's capability to perform integrated reporting. The analysis used in testing the hypothesis is multiple linear regression analysis. Results show that company’s size has positive and significant connection and stakeholder’s pressure has negative and significant connection with the company’s capability in performing integrated reporting. In contrast, level of company’s profitability, company’s managerial ownership, and company’s institutional ownership did not have enough connection with company’s capability in performing integrated reporting.